(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article deals with existential themes and eschatological issues in the novel of Smagul Elubay «The Frailworld» that is the third part of the trilogy «The lonely house». The character of the main personage Edige who shows the true nature of his being in the moment of crisis, in the border situation is analyzed. Mystical-philosophical reasons, symbolic images are considered in close connection with the artistic world of the novel.